PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PADA BANK MUAMALAT KC SURABAYA DARMO - Nurul fatma hasan; Amirotul (Universitas Haji Sumatera Utara, 2023)
In an increasingly competitive banking industry, banks are trying to increase customer satisfaction. In order for customers to transact calmly, banks need to carry out service activities that satisfy customers, such as facilities, polite and fast responses, ethics and courtesy. The purpose of this study was to determine the effect of credibility, responsiveness, certainty, empathy, and direct evidence on customer satisfaction at Bank Muammarat KC Surabaya Darmo. Quantitative research is used in this type of research. The data analysis technique used is plausibility test, reliability test, classic hypothesis test, multiple regression analysis, correlation coefficient, coefficient of determination (R2), and hypothesis testing. Based on the results of the subtest survey, at Bank Muamalat KC Surabaya Darmo, trust, responsiveness, security, and empathy have no effect on customer satisfaction, while direct evidence has a positive effect on customer satisfaction. Simultaneous testing found that service quality simultaneously influences customer satisfaction at Bank Muammarat KC Darmo Surabaya. Keywords : Service Quality and Customer Satisfaction